2015
DOI: 10.1111/hojo.12111
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Bodies: The New Victims of Unethical Experimentation

Abstract: Despite a number of beneficent outcomes, clinical trials on human subjects have exposed some of the worst forms of state crime, most notably in Nazi Germany. Even with the subsequent establishment of guidelines for the protection of human subjects, such as the Nuremberg Code, clinical trials resulting in death and injury is a continuing feature of medical research, especially as Western states outsource more trials to the private sector where profit margins often trump personal safety. Focusing on the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…Along with Tombs (2012), I would argue that this suggests that the regulatory system is benefitting those corporations that are seeking to enlarge the capital accumulation of the ownership of these organizations. Thus, contrary to the case studies reviewed in this article where state-corporate crime scholars have suggested that this practice emerges because of a lack of regulations (Rawlinson and Yadavendu 2015;Green et al 2007;Leighton 2016), the two cases examined herein indicate that Starbucks and Fiat use tax regulations in a manipulative way (research question 1). The manipulative use of the tax law, as illustrated here, reflects the unlimited influence of powerful actors who seek to profit at any cost and the weakness of laws that prevent the criminalization of powerful perpetrators, which is evidenced by the fact that they are not indicted in criminal courts (Kramer et al 2002: 266).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Along with Tombs (2012), I would argue that this suggests that the regulatory system is benefitting those corporations that are seeking to enlarge the capital accumulation of the ownership of these organizations. Thus, contrary to the case studies reviewed in this article where state-corporate crime scholars have suggested that this practice emerges because of a lack of regulations (Rawlinson and Yadavendu 2015;Green et al 2007;Leighton 2016), the two cases examined herein indicate that Starbucks and Fiat use tax regulations in a manipulative way (research question 1). The manipulative use of the tax law, as illustrated here, reflects the unlimited influence of powerful actors who seek to profit at any cost and the weakness of laws that prevent the criminalization of powerful perpetrators, which is evidenced by the fact that they are not indicted in criminal courts (Kramer et al 2002: 266).…”
Section: Discussioncontrasting
confidence: 68%
“…Several case studies are worth noting. For example, an Indian case study conducted by Rawlinson and Yadavendu (2015) revealed the lack of regulations on the operations of multinational pharmaceutical companies that conduct the offshoring of clinical human trials. A Tasmanian case study documented by Green et al (2007) illustrated the problem of regulatory capture of the forest authority that facilitated illegal logging in this territory.…”
Section: Previous Researchmentioning
confidence: 99%